305 Genetic parameters of meat quality and carcass composition traits in crossbred swine. (7th December 2018) - Khanal, P; Maltecca, C; Schwab, C; Gray, K; Tiezzi, F
Abstract: The objective of this study was to estimate the heritabilities and genetic correlations of meat quality and carcass composition traits in 2 commercial crossbred swine populations: The Maschhoffs (TML) and Smithfield Premium Genetics (SPG). The TML dataset consisted of 1, 255 crossbred individuals genotyped and phenotyped for meat quality (MQ), carcass yield (CY) and carcass weight (CW) traits. The SPG population included over 30, 000 crossbred individuals phenotyped for a subset of MQ, CY and CW traits, and 1, 156 sires genotyped. The two populations were analyzed separately with the use of multiple-trait genomic models. For the TML dataset, models included fixed effects of dam line, contemporary group (CG), gender, as well as a random additive genetic effect and pen nested within CG. For the SPG dataset, fixed effects included parity, gender and CG, as well as a random additive genetic effect and harvest group. Analyses were conducted using the BLUPf90 suite of programs. Bivariate analyses were used to estimate correlations among traits. Heritabilities [confidence interval] for CY traits (0.17[0.09, 0.25] to 0.45[0.36, 0.55]) were higher than CW (0.14[0.06, 0.23] to 0.30[0.20, 0.41]). For MQ traits, heritabilities ranged from low to moderate having highest estimate for intramuscular fat: 0.52[0.40, 0.62]. Most of the genetic correlations were significant and ranged from -0.07[-0.14, -0.02]) to -0.70[-0.85, -0.84], 0.50[0.32, 0.79] to 0.81[0.78, 0.82] and -0.10[-0.02, -0.04] to -0.96 [-1.00, -0.83] respectively among CY, CW and MQ traits. The genetic correlations of MQ and carcass composition traits ranged from moderate to high in both directions. The genetic parameter estimates indicate that a multi-trait approach should be considered for selection programs aimed at carcass quality and composition in commercial crossbred swine population.